2021
DOI: 10.1039/d1dt02473f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostannylation of carbon dioxide by a hydridostannylene molybdenum complex

Abstract: Reaction of the aryltin(ii) hydrides with molybdenum carbonyl afforded Mo(CO)5{Sn(AriPr6)H}, (1), or Mo(CO)5{Sn(AriPr4)(THF)H} (2), respectively, in which 1 reacted with carbon dioxide, to yield Mo(CO)5{Sn(AriPr6)(κ2-O,O′-O2CH)}, (3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 61 publications
5
22
0
Order By: Relevance
“…Insertion of olefines and carbon dioxide into the Sn–H bond of low valent organotinhydrides was studied by Power et al and for a coordinated organohydrido germylene another example of styrene insertion is presented in the literature. 14,29,81…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insertion of olefines and carbon dioxide into the Sn–H bond of low valent organotinhydrides was studied by Power et al and for a coordinated organohydrido germylene another example of styrene insertion is presented in the literature. 14,29,81…”
Section: Resultsmentioning
confidence: 99%
“…Insertion of olenes and carbon dioxide into the Sn-H bond of low valent organotinhydrides was studied by Power et al and for a coordinated organohydrido germylene another example of styrene insertion is presented in the literature. 14,29,81 In the case of the low valent lead cation the tungstenocene dihydride adduct 3b does not exhibit a hydrogen atom migration from tungsten to lead as in the case of the tin compound 3a. Lead adduct 3b was readily deprotonated at rt by Me NHC to yield the plumbylene complex 5b (Scheme 8).…”
Section: Tablementioning
confidence: 97%
See 1 more Smart Citation
“…25,26 In 2021, this group showed that the THF donor ligand in [Mo(CO) 5 THF] could be displaced by a hydridostannylene, [Ar iPr6 SnH], to give Mo(CO) 5 {Sn(Ar iPr6 )H}. 27 This complex was then shown to effect facile hydrostannylation of CO 2 , and catalytic hydroboration of CO 2 was achieved with pinacolborane. These results were in contrast to the lack of catalytic activity for CO 2 reduction by the parent tin hydride, {Ar iPr6 Sn(μ-H)} 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…14,15 In an effort to change the electronics and structural platform for tin hydride complexes, there have been reports of tin hydride complexes coordinated to transition metals, featuring tin in the +2 oxidation state, utilizing Lewis base/Lewis acid pairs for stabilization. [16][17][18][19][20][21] Overall, these advancements in the tin chemistry platform specifically regarding the production of low valent and highly reduced tin species have led to the observation of transition-metal like reactivity of tin, including activation of small and unsaturated molecules. 22 In an effort to expand on the known structural and reaction chemistry of tin, we sought to investigate the impacts of supporting different tin functional groups on polynuclear transition metal clusters.…”
Section: Introductionmentioning
confidence: 99%